Fourteenth Intersociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems (ITherm) 2014
DOI: 10.1109/itherm.2014.6892332
|View full text |Cite
|
Sign up to set email alerts
|

Improving cooling efficiency of servers by replacing smaller chassis enclosed fans with larger rack-mount fans

Abstract: As a common practice in the data center industry, chassis fans are used to direct air flow independent from neighboring servers. However, these fans are less efficient compared to larger rack level counterparts and also operate at higher sound levels. In this study, a novel approach is proposed whereby the smaller chassis enclosed fans are replaced with an array of larger fans, installed behind the stacked servers that share air flow.As a baseline study for comparison of the current scenario, a CPU dominated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…A previous study by the authors of this work showed computational fluid dynamics evidence based on empirical data that significant savings in fan energy are possible through consolidation of smaller, internal server fans to a larger rack-based fan configuration [8]. Additional details of this previous study included findings that a failure of a single fan out of the four in the server under study has the same impact on die temperatures, irrespective of the location of the failed fan.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…A previous study by the authors of this work showed computational fluid dynamics evidence based on empirical data that significant savings in fan energy are possible through consolidation of smaller, internal server fans to a larger rack-based fan configuration [8]. Additional details of this previous study included findings that a failure of a single fan out of the four in the server under study has the same impact on die temperatures, irrespective of the location of the failed fan.…”
Section: Introductionmentioning
confidence: 83%
“…A simple wooden frame and acrylic panel were constructed to hold the larger fan array at the back of the servers. A previous computational study by the authors indicated that a minimum distance of 20 mm was needed between the back of the servers and the fan array to ensure uniform distribution of airflow between all four servers [8]. Following this minimum requirement, the fan array for this study was placed 25.4 mm (1 in) from the rear of the servers.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary work [14] predicted savings of up to 55% in cooling power by replacing smaller, chassis enclosed (60 mm) fans with larger rack-mount units for a stack of four servers. The present studies (parts I and II) advance this work by experimentally validating maximum possible savings through deployment of 80 mm and 120 mm fans.…”
Section: Introductionmentioning
confidence: 99%